A Content Analysis of the Reading Activities in â€œBright 2â€an English Textbook for Junior High School Students - Sucipto Sucipto; Septian Dwi Cahyo (Universitas Ahmad Dahlan, 2019)
This study aimed to analyze reading activities in â€œBright 2â€ an English textbook for junior high school students grade VIII in Indonesia by using Bloomâ€™s revised taxonomy. A content analysis was conducted to achieve the research purpose. The findings show that the textbook has dominant reading activities on the cognitive process â€œanalyzeâ€ 27% and â€œapplyâ€ 21% of the total 145 reading activities, respectively. Â The number of higher and lower cognitive processes in this textbook is almost balanced on 49% of higher order thinking skills and 51% of lesser order thinking skills correspondingly. There is a slight difference between the number higher thinking process and lower thinking process since most reading activities are on â€œanalyzeâ€, which is belong to the higher thinking process while the second most frequent reading activities are â€œapplyâ€, the lower thinking process. Meanwhile, â€œapplyâ€ and â€œanalyzeâ€ is placed on the 3rd and 4th in the taxonomy, it means that the textbook emphasizes the middle cognitive thinking process of Bloomâ€™s revised taxonomy, which is formed by â€œapplyâ€ and â€œanalyzeâ€Â thinking process.